Synthesis, physicochemical and biological evaluation of N-dealkylated metabolites of antimalarial pyrido[1,2-a]benzimidazoles and related compounds containing a Mannich base side-chain - Ferger, Richard (Department of Chemistry, 2020)
Malaria is one of the leading causes of deaths worldwide. Despite strategic implementations aimed at decreasing mortality and morbidity rates in recent decades, this plasmodial disease continues to impact public health and the economies of developing countries. Furthermore, the emergence of resistance toward current antimalarial treatments increases the necessity for the development of novel antimalarials. The benzimidazole scaffold is an extensively researched privileged scaffold in medicinal chemistry because of its capacity to interact with numerous biological systems in various diseases, including malaria. Based on previous metabolite identification studies in liver microsomes, a new series of pyrido[1,2-a]benzimidazole (PBI) metabolites containing Mannich base side-chains were designed and synthesized. Their in vitro parasite (Plasmodium falciparum) growth and β-hematin formation inhibition activities, turbidimetric solubility, cytotoxicity, and microsomal metabolic stability in mouse liver microsomes were evaluated. To investigate structure activity relationships (SARs), the study was broadly diversified into two series (SAR-1 and SAR-2). Mannich base side-chains from SAR-1 were designed and synthesized as hypothesized N-dealkylated metabolites. In SAR-2, hypothesized N-dealkylated metabolites were compared with their respective parent compounds with a focus on modifications around the PBI core. The most potent analogues exhibited sub-micromolar activity (50% inhibitory concentration (IC50) < 1 µM) against the drug-sensitive NF54 strain of Plasmodium falciparum. Some compounds showed high activity against early- and late-stage gametocytes, the sexual stage transmissible forms of the parasite. Overall, compounds in this series were more active against early-stage gametocytes than latestage gametocytes, thus indicating stage-specificity. All but three of the analogues synthesized were potent inhibitors of β-hematin formation. Most compounds showed no cytotoxicity against HepG2 and Chinese hamster ovarian (CHO) cells. Inclusion of Mannich base side-chains influenced the in vitro microsomal metabolic stability of compounds. As expected, N-dealkylated (desethyl) metabolites showed greater metabolic stability relative to their equivalent parent compounds.